LITERATURE REVIEW : Intervensi Short Wave Diathermy Dan Calisthenic Exercise Untuk Mengurangi Nyeri Dan Meningkatkan Aktivitas Fungsional Pada Penderita Osteoarthritis Lutut Kronis - Taruna Nur Ahmad, (2020)
Objective: Reduce pain and increase the functional activity of people with chronic knee osteoarthritis. This literature study aims to review the literature, journals, articles, or research results on the topic of short wave diathermy and calisthenic exercise interventions to reduce pain and improve the functional activity of chronic knee osteoarthritis sufferers. Methods: Search for sources of literature, journals, articles, research results in several databases such as Google Scholar, Science Direct, Elsevier, PEDro, PubMed by using certain keywords in the period 2015-2020. From the literature search results, 11 articles were obtained and only 5 articles met the source inclusion criteria. The methodological quality assessment of 5 articles was assessed using the Scimago Journal & Country Rank (SJR). Analysis of 5 journals was carried out based on the suitability of the topic, the research methods used, samples, interventions, instruments / parameters, and the results of each article. Results: After reviewing the literature as many as 5 articles showed that short wave diathermy can reduce pain and calisthenic exercise can increase functional activity. Conclusion: Short wave diathermy can reduce pain and calisthenic exercise can increase functional activity in patients with chronic knee osteoarthritis.